CRITICAL THINKING SKILLS AND DISPOSITIONS IN THE EDUCATIONAL CONTEXT: DIFFERENT VIEWS - Marco Tulio Rodríguez Sandoval, Gianny Bernal Oviedo, Luz Stella Fuentes Fuentes, Análida Pérez Cardona, Vanessa Pérez Peñalosa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This review article presents an overview of the cognitive and operative dimension of critical thinking and, in turn, of this type of thinking from a pedagogical approach to develop it in an educational context. To do the above, a review of different articles is made with which it is possible to clarify that the skills are identifiable, teachable and are learned; and that by themselves they have a cognitive component, but that this must be accompanied by the non-cognitive (dispositions of thought). Likewise, it is established that there is no universal or exclusive concept of critical thinking, because each author defines it depending on the skills and the respective threads with which they relate. In this sense, the following skills are proposed to work in the university educational context: analyze, synthesize, solve problems and evaluate, which can be applicable to any context: personal, professional or vital.